Michael Gorbovy as an Organizer of the Scouting Movement in Gutsulschina (the Beginning of the XX Century) - Didukh , Iryna (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The Ukrainian scouting movement on western Ukrainian territories reached the highest level during the interwar period. Despite the relative integrity it had its own features in Galicia, Volyn', on Bukovyna, Transcarpathia. As living conditions turned out to be peaceful, old plast centres started to form in schools. "Plast" in Galicia was an example of inheritance and incentive to the development on other western Ukrainian territories and in emigration. The figure of famous Hutsul plastun Michael Gorbovy (1896 – 1941) is very interesting and multidimensional. Indeed, it is a symbolic name in the history of Ukrainian scout organization. He was a member of many national public organizations. With his name economic and cooperative activities of "Plast" in Gutsulschina are connected. He was the organizer of craft departments of "Plast". The unicity of this disjoint person is expressed in his great love for Ukraine and responsibility for its future. Gorbovy considered physical, moral and national-patriotic education of children and youth as his main task. He strived to spread the idea of Ukrainian scouting among wide groups of people. For this work on 22th of May, 1924 he was awarded with a plast title of a scoutmaster. Michael Gorbovy formed national consciousness, high spirituality, love of God and Ukraine among youth for the "great aim" which is to build an independent Ukrainian nation. Experts qualify current spiritual and moral state of the Ukrainian society as "crisis". School is not able to fill the educational vacuum which has appeared after the elimination of the Pioneer and Komsomol organizations. No new alternative children's institutions have been suggested. In such a difficult situation the experience of the activity of the Ukrainian scouting movement may be useful. Creative and practical achievements of "Plast" leaders as key figures and main carriers of the plast's educational methods are especially important. These include a figure of the leader of the Ukrainian Scouting movement in Gutsulschina, Michael Gorbovy